Alizapride and ondansetron for the prevention of postoperative nausea and vomiting in patients undergoing laparoscopic gynaecological surgery: A double-blind, randomised, placebo-controlled noninferiority study. Issue 2 (February 2016) - Dewinter, Geertrui; Teunkens, An; Vermeulen, Kristien; Devroe, Sarah; Van Hemelrijck, Jan; Meuleman, Christel; Vergote, Ignace; Fieuws, Steffen; Van de Velde, Marc; Rex, Steffen
Abstract : BACKGROUND: Postoperative nausea and vomiting (PONV) can be prevented. Alizapride is an established antiemetic that may be effective in this role. OBJECTIVE: Our primary objective was to test the hypothesis that alizapride is noninferior to ondansetron for the prophylaxis of PONV. DESIGN: A randomised, placebo-controlled, double-blinded noninferiority study. SETTING: University hospitals of Leuven, Belgium, from November 2008 to July 2011. PATIENTS: A total of 523 patients undergoing laparoscopic gynaecological surgery were included in the study. Reasons for exclusion were American Society of Anesthesiologists (ASA) greater than 2, hypersensitivity to the study medication, pregnancy, mental disorders, psychiatric illness or consumption of antiemetic drugs within 24 h before initiation of the study. INTERVENTION: Patients received either alizapride 100 mg, ondansetron 4 mg or placebo intravenously 30 min before the end of surgery. MAIN OUTCOME MEASURES: The main outcome measures included the incidences of postoperative nausea (PON) and postoperative vomiting (POV) during the stay in the postanaesthetic care unit (PACU), with noninferiority testing for alizapride versus ondansetron. The region of noninferiority was defined as a relative difference in incidence of 25%. Secondary outcome was the incidence of PONV in the PACU and after 24 h. RESULTS: In the alizapride group, 32% of the patients experienced PON during the PACU stay, compared with 28% in the ondansetron group [relative risk 1.13, 90% confidence interval (CI) 0.87 to 1.46], exceeding the predefined margin of noninferiority. With respect to the incidences of POV during the PACU stay, 12.8% of the patients randomised to receive alizapride experienced POV, compared with 7.7% of who received ondansetron (relative risk 1.67, 90% CI 1.00 to 2.87). The incidences of PON and POV in the placebo group during the PACU stay were 34.2 and 9.8%, respectively. The 24-h incidences of PONV were lower than expected in this high-risk group of patients and were similar at 39.3, 36.8 and 31.5% in the placebo, alizapride and ondansetron groups, respectively ( χ 2, P  = 0.36). Patients treated with ondansetron required significantly less rescue medication than placebo-treated patients ( P  = 0.035). Due to the lower than expected incidences of PONV in this study, the power to conclude any noninferiority of alizapride was reduced to only 41%. CONCLUSION: We found no evidence to support the noninferiority of alizapride 100 mg when compared with ondansetron 4 mg for the intraoperative prophylaxis of PONV. However, the lower than expected incidences of PONV reduced the power of this study to conclude noninferiority or confirm significant beneficial effects for either antiemetic for PON and POV during the PACU stay. TRIAL REGISTRATION: Eudra CT 2008-004789-20